Vertebral artery dissection associated with familial Mediterranean fever and Behçet's disease. Issue 5 (4th April 2019) - Ishikawa, Hidehiro; Shindo, Akihiro; Ii, Yuichiro; Sakano, Shoko; Asahi, Masaru; Matsuura, Keita; Kishida, Dai; Umino, Maki; Maeda, Masayuki; Tomimoto, Hidekazu
Abstract: Vertebral artery dissection and recurrent meningitis are rare complications in Behçet's disease. Behçet's disease may be associated with familial Mediterranean fever. Here, we describe a 52‐year‐old woman with severe headache who exhibited recurrent meningitis and vertebral artery dissection. Cerebrospinal fluid showed high levels of interleukin‐6. Magnetic resonance imaging revealed right vertebral artery dissection. The patient had three heterozygous mutations in the familial Mediterranean fever gene ( MEFV) gene. She fulfilled criteria for diagnosis of Behçet's disease and familial Mediterranean fever. In conclusion, mutations of the MEFV gene may cause neuro‐inflammatory disorders and cerebrovascular disorders by reducing anti‐inflammatory activity of pyrin.